Understanding the social determinants of individuals’ health in an area of Hyderabad: a cross sectional study - Rahmath, Shaik Sadiya; Nimrah, Safia; Ahmad, Sultan Rizwan; Madhipati, Sai Krishna (International Journal Of Community Medicine And Public Health, 2023)
Background: The population of India is diverse and heterogeneous, comprising different social groups like castes, religions, languages, and regions. It faces many challenges, such as poverty, illiteracy, malnutrition, lack of access to health care, sanitation, education, and infrastructure. Due to lack of proper knowledge, there is an inadequate health seeking behaviour among the people about the importance of health. This study helps us to know the most prevalent morbid conditions and how health status affects various aspects of life. Methods: A survey was conducted by students of Deccan College of Medical Sciences under the guidance of the department of community medicine. A total of 200 families with 1101 individuals were surveyed on various parameters in quality of life, immunization, literacy and marital status. The data was analysed using descriptive statistics. Results: In this study, 554 were males (50.31%) and 547 females (49.68%). Predominant age group was of 16-45 years (54.58%) and the least belonged to above 60 (3.17%). 12.17% individuals were illiterate while only 6.53% pursued higher education. There were 31 (51.67%) males and 29 (48.33%) females that were fully immunized and 3% females were not immunized. Hypertension exhibited highest prevalence at 41.36%. Majority of the population fell into socioeconomic status class III (41.32%). Conclusions: Community diagnosis is an effective tool in assessing the health status of an area. It can help the health officials and healthcare centres to take appropriate measures suitable to handle the problems prevailing in that area.